Investment Decisions in Business Strategy: The Role of Leverage, Sales Growth, Liquidity, Profitability, and Cash Flow - Ridzal, Nining Asniar; Amiruddin, Amiruddin; Syarifuddin, Syarifuddin; Darmawati, Darmawati; HS, Rahmawati (Pusat P2M Politeknik Negeri Batam, 2024)
The purpose of this study is to ascertain how investment decisions in technology businesses listed on the Indonesia Stock Exchange are influenced by factors such as leverage, cash flow, profitability, sales growth, and liquidity. By gathering annual reports and financial report data, this study was carried out on technology companies listed on the Indonesia Stock Exchange (BEI). The population of this research is 44 technology sector companies listed on the IDX. The sample was determined using the Purposive Sampling method using criteria. There are six companies that meet the criteria, and this research was conducted for five years, so there is a total of 30 data in this research. The type of data used is quantitative data in the form of financial reports and annual reports of technology sector companies listed on the IDX for the 2018-2022 period, which is secondary data from this research. The data analysis method used in this research is a quantitative descriptive analysis method with Multiple Linear Regression analysis using the SPSS ( Statistical Package for the Social Sciences) statistical tool. The findings of this research are that leverage influences investment decisions . The sales growth variable has a positive effect on investment decisions . The liquidity variable has a positive effect on investment decisions with value significant of 0.041 . Meanwhile, the profitability and cash flow variables partially have no effect on investment decisions, with significance values of 0.112 and 0.113 respectively .